Analysis of Toxigenic Fusarium Species Associated with Wheat Grain from Three Regions of Russia: Volga, Ural, and West Siberia - Gagkaeva, Tatiana (Toxins (Basel), 2019)
Wheat grains collected in three regions of Russia—Volga, Ural, and West Siberia—were analyzed for triangulation of methods in analysis of toxigenic Fusarium species. The presence of fungi and quantitative content of their biomass were detected by using various analytical methods, including a mycological and immunochemical methods, and quantitative PCR. Additionally, an enzyme-linked immunosorbent assay and high-performance liquid chromatography with tandem mass spectrometry were applied for determination of mycotoxins. Regional differences were found regarding the contamination of wheat grain by Fusarium fungi and their toxins. The most important observation was the detection of F. graminearum in the Ural and West Siberian regions, where this pathogen had not been found previously. A maximum damaged grains by F. graminearum and F. sporotrichioides was found in the grain samples from West Siberia. The DNA of F. graminearum was detected in 19.2% and DNA of F. sporotrichioides was found in 84.1% of the analyzed grain samples. The amount of Fusarium antigens in the grain samples from the West Siberian region was 7–8 times higher than in the grain samples from the other two regions. Significant contamination of the grain with deoxynivalenol and T-2/HT-2 toxins (maximum contents were 2239 ppb and 199 ppb, respectively) was detected in the West Siberian region.